2010
DOI: 10.1007/s13225-010-0022-8
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity of culturable fungi associated with two marine sponges: Haliclona simulans and Gelliodes carnosa, collected from the Hainan Island coastal waters of the South China Sea

Abstract: The diversity and biological activities of fungi associated with the two sponges, Haliclona simulans and Gelliodes carnosa, were investigated using a culturedependent method followed by analysis of the fungal rDNA-ITS sequences. The two sponges were collected from the coastal waters of Lingshui Bay of Hainan Island in the South China Sea. A total of 37 independent fungal isolates corresponding to 30 different species were obtained from the two sponges. Nearly two thirds of the strains (n=24, 64.9%) had close a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 86 publications
2
41
0
Order By: Relevance
“…Culture-based and isolationindependent methods have shown a large diversity of fungi associated with sponges and have demonstrated that fungal community composition differs between sponge species and the surrounding water (Li and Wang 2009;Gao et al 2008). The majority of the identified cultivable fungi associated with sponges belongs to the phylum Ascomycota with Eurotiales and Hypocreales as the most abundant orders within the phylum (Li and Wang 2009;Baker et al 2009;Liu et al 2010;Ding et al 2011;Wiese et al 2011). In addition, the order Capnodiales was the major representative in two sponge species classified in the order Haplosclerida collected in the South China Sea (Liu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Culture-based and isolationindependent methods have shown a large diversity of fungi associated with sponges and have demonstrated that fungal community composition differs between sponge species and the surrounding water (Li and Wang 2009;Gao et al 2008). The majority of the identified cultivable fungi associated with sponges belongs to the phylum Ascomycota with Eurotiales and Hypocreales as the most abundant orders within the phylum (Li and Wang 2009;Baker et al 2009;Liu et al 2010;Ding et al 2011;Wiese et al 2011). In addition, the order Capnodiales was the major representative in two sponge species classified in the order Haplosclerida collected in the South China Sea (Liu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the identified cultivable fungi associated with sponges belongs to the phylum Ascomycota with Eurotiales and Hypocreales as the most abundant orders within the phylum (Li and Wang 2009;Baker et al 2009;Liu et al 2010;Ding et al 2011;Wiese et al 2011). In addition, the order Capnodiales was the major representative in two sponge species classified in the order Haplosclerida collected in the South China Sea (Liu et al 2010). Overall, there is strong evidence that the diversity of genera and the number of isolates per sponge varies greatly among different locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only bootstrap values above 50% were shown, and only those above 70% were considered significant (Liu et al 2010). The phylogenetic tree was rooted using Chytriomyces hyalinus as an outgroup (GenBank accession number DQ536499.1).…”
Section: Phylogenetic Relationship Analysesmentioning
confidence: 99%
“…Fungi associated with marine sponges have been frequently observed from temperate, tropical and polar waters (Gao et al 2008;Wang et al 2008;Baker et al 2009;Lie & Wang 2009;Liu et al 2010;Menezes et al 2010;Paz et al 2010;Ding et al 2011;Wiese et al 2011;Zhou et al 2011;Suryanarayanan 2012;Thirunavukkarasu et al 2012;Henriquez et al 2013). Their diversity was mainly explored in order to assess the potential for the production of novel active secondary metabolites with biological activity (Höller et al 2000;Henriquez et al 2013) and, consequently, the real biological significance of the relationships remains unclear.…”
Section: Introductionmentioning
confidence: 99%